2015
DOI: 10.3109/15368378.2015.1036072
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of DNA information through water and electromagnetic waves

Abstract: The experimental conditions by which electromagnetic signals (EMS) of low frequency can be emitted by diluted aqueous solutions of some bacterial and viral DNAs are described. That the recorded EMS and nanostructures induced in water carry the DNA information (sequence) is shown by retrieval of that same DNA by classical PCR amplification using the TAQ polymerase, including both primers and nucleotides. Moreover, such a transduction process has also been observed in living human cells exposed to EMS irradiatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 30 publications
6
101
0
Order By: Relevance
“…Our standpoint is consistent with previous experimental work [3][4][5][6] that has shown that some DNAs in water dilutions emit electromagnetic waves of low frequency (from hundreds to 3 kHz) which could be triggered, as in a resonance phenomenon, by an outside excitation, such as the Schumann waves [19]. Experimental peaks of Schumann waves are at 7.83, 14.3, 20.8, 27.3, and 33.8 Hz; the peak near 7 Hz is the one found to be minimally active in the case discussed here (for further details see [3][4][5][6]).…”
Section: The Taq-dna Interaction and Open Questionssupporting
confidence: 82%
See 4 more Smart Citations
“…Our standpoint is consistent with previous experimental work [3][4][5][6] that has shown that some DNAs in water dilutions emit electromagnetic waves of low frequency (from hundreds to 3 kHz) which could be triggered, as in a resonance phenomenon, by an outside excitation, such as the Schumann waves [19]. Experimental peaks of Schumann waves are at 7.83, 14.3, 20.8, 27.3, and 33.8 Hz; the peak near 7 Hz is the one found to be minimally active in the case discussed here (for further details see [3][4][5][6]).…”
Section: The Taq-dna Interaction and Open Questionssupporting
confidence: 82%
“…As Schrödinger observed for living matter in general (and his remarks apply equally well to the case of PCR processes), the attempt to explain the high efficiency in terms of ordering generated by "statistical mechanisms" * would be "the classical physicist's expectation that far from being trivial, is wrong" * , and "it needs * [18] (p. 47) * [18] (p. 19) no poetical imagination but only clear and sober scientific reflection to recognize that we are here obviously faced with events whose regular and lawful unfolding is guided by a mechanism entirely different from the probability mechanism of physics" * . We propose in this paper and in [5,6] that a third party intervenes in the DNA-enzyme interaction processes, which is organized (coherent) water, and we show how this fits well with the general gauge theory paradigm of quantum fields [15,16] (see also [7][8][9][10][11]). …”
Section: The Taq-dna Interaction and Open Questionsmentioning
confidence: 78%
See 3 more Smart Citations